2014
DOI: 10.1161/circgenetics.113.000486
|View full text |Cite
|
Sign up to set email alerts
|

Novel α-Actinin 2 Variant Associated With Familial Hypertrophic Cardiomyopathy and Juvenile Atrial Arrhythmias

Abstract: Background— Next-generation sequencing might be particularly advantageous in genetically heterogeneous conditions, such as hypertrophic cardiomyopathy (HCM), in which a considerable proportion of patients remain undiagnosed after Sanger. In this study, we present an Italian family with atypical HCM in which a novel disease-causing variant in α-actinin 2 (ACTN2) was identified by next-generation sequencing. Methods and Results— A large family spanning 4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 73 publications
(58 citation statements)
references
References 42 publications
0
58
0
Order By: Relevance
“…5 Specific sarcomeric gene mutations have recently been described in atypical forms of HCM that relate to juvenile onset of AF in these patients. 17 Even polymorphisms in nonsarcomeric genes, encoding for proteins involved in the renin-angiotensin-aldosterone system and collagen synthesis, have shown to act as HCM disease modifiers, increasing the likelihood of AF development. 18 Therefore, it is not unexpected that AF often complicates the natural course of HCM, translating into a significant morbidity and mortality burden.…”
Section: Discussionmentioning
confidence: 99%
“…5 Specific sarcomeric gene mutations have recently been described in atypical forms of HCM that relate to juvenile onset of AF in these patients. 17 Even polymorphisms in nonsarcomeric genes, encoding for proteins involved in the renin-angiotensin-aldosterone system and collagen synthesis, have shown to act as HCM disease modifiers, increasing the likelihood of AF development. 18 Therefore, it is not unexpected that AF often complicates the natural course of HCM, translating into a significant morbidity and mortality burden.…”
Section: Discussionmentioning
confidence: 99%
“…Our research identified another likely pathogenic mutation of ACTN2 which may be related to overlap phenotypes of cardiomyopathy and arrhythmias. This study provides a new case to perform further analyses on the relationship between ACTN2 mutations and overlap phenotypes, like the reported mutations p.A119T and M228T [Bagnall et al, 2014;Girolami et al, 2014]. In conclusion, we employed whole-exome sequencing in combination with a filtering strategy for cardiomyopathy-and arrhythmia-related genes to discover the genetic factors in a DCM family with brief syncope, ventricular tachycardia, and SCD.…”
Section: Discussionmentioning
confidence: 86%
“…However, most ACTN2 mutations were identified in HCM [Chiu et al, 2010;Haywood et al, 2016], and less mutations have been detected in DCM patients [Mohapatra et al, 2003;Zimmerman et al, 2010;Gonzalez-Garay et al, 2013]. What is more, only 2 reports found that variants of ACTN2 can lead to overlap phenotypes of cardiomyopathy and arrhythmias [Bagnall et al, 2014;Girolami et al, 2014]. Previous studies revealed that ACTN2 may play multiple functions in the Z-disc.…”
Section: Discussionmentioning
confidence: 99%
“…Exome sequencing has been used to identify a mutation in the α-actinin-2 gene in a family associated with idiopathic ventricular fibrillation, left ventricular noncompaction and sudden death [23]. A targeted next-generation sequencing approach allowed the identification of a novel α-actinin-2 variant associated with midapical hypertrophic cardiomyopathy and juvenile-onset atrial fibrillation [24]. One study showed remodeling of the sarcomeric cytoskeleton in cardiac ventricular myocytes during heart failure and after cardiac resynchronization therapy [25].…”
Section: Discussionmentioning
confidence: 99%